2003
DOI: 10.1038/sj.ijo.0802192
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance but not visceral adipose tissue is associated with plasminogen activator inhibitor type 1 levels in overweight and obese premenopausal African-American women

Abstract: OBJECTIVE:To compare plasma plasminogen activator inhibitor type 1 (PAI-1) levels and to examine the association of PAI-1 with visceral adiposity and other components of the metabolic syndrome in overweight and obese premenopausal African-American (AA) and Caucasian (CC) women. DESIGN: Cross-sectional study. SUBJECTS: 33 CC and 23 AA healthy, overweight and obese, premenopausal women (age 19 -53 y, body mass index 28.1 -48.9 kg=m 2 ). MEASUREMENTS: Body mass index, sagittal diameter, waist circumference, perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
3
14
1
1
Order By: Relevance
“…However, African American women do not commonly present with hypertriglyceridemia (Metcalf et al, 1998). Despite often having higher HDL-C levels than white people, African American women still suffer unexplained cardiovascular health disparities Solano, Perry, Wang, Ross, & Goldberg, 2003). In order to determine the presence of insulin resistance that was present in the participants of this study, we computed a HOMA-IR (Matthews et al, 1985;Monzillo & Hamdy, 2003;Wallace, Levy, & Matthews, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, African American women do not commonly present with hypertriglyceridemia (Metcalf et al, 1998). Despite often having higher HDL-C levels than white people, African American women still suffer unexplained cardiovascular health disparities Solano, Perry, Wang, Ross, & Goldberg, 2003). In order to determine the presence of insulin resistance that was present in the participants of this study, we computed a HOMA-IR (Matthews et al, 1985;Monzillo & Hamdy, 2003;Wallace, Levy, & Matthews, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from our study showed a non-significant positive association between BMI and PAI-1 (r = 0.21, p = 0.15) as well as a non-significant relationship between the number of days participants engaged in moderate physical activity per week and PAI-1. These results are consistent with findings reported by Solano, Perry, Wang, Ross, and Goldberg (2003), suggesting that relationships reported in white populations differs in African-Americans. Solano et al, (2003), in a cross-sectional study of overweight and obese premenopausal African American and Caucasian women aged 19 to 53 years, examined the association of PAI-1 with visceral adiposity and other components of the metabolic syndrome.…”
Section: Correlations Between Obesity Physical Activity and Thrombosupporting
confidence: 83%
“…These results are consistent with findings reported by Solano, Perry, Wang, Ross, and Goldberg (2003), suggesting that relationships reported in white populations differs in African-Americans. Solano et al, (2003), in a cross-sectional study of overweight and obese premenopausal African American and Caucasian women aged 19 to 53 years, examined the association of PAI-1 with visceral adiposity and other components of the metabolic syndrome. They found no significant association between PAI-1 and any of these variables (BMI, visceral adipose tissue, glucose, systolic blood pressure, diastolic blood pressure, triglyceride, HDL cholesterol) in African American women, despite their findings of a strong association between these metabolic variables and PAI-1 in Caucasian women.…”
Section: Correlations Between Obesity Physical Activity and Thrombosupporting
confidence: 83%
See 2 more Smart Citations